The dimension of physical education - Ciccomascolo, Lori E.; Sullivan, Eileen Crowley (Jones & Bartlett Learning, 2013)
The Dimensions of Physical Education is an all-in-one reader that addresses important issues in physical, health, and sport education. The text assists students in learning the designated content by providing reader-friendly, scholarly articles and letters that discuss the real issues in the field. Instructors are encouraged to use the articles to challenge students to think about how all of the dimensions of physical and health education connect to each other. The format of the text allows instructors to select and teach the content of the chapters in any order that meets the needs of their students and courses.